THE EFFECT OF USING VLOGGING TASK IN ENGLISH SPEAKING PERFORMANCE BY STUDENTS OF SMA GAJAH MADA MEDAN - Mikael Aprillio Sihombing; Ernawati Tampubolon; Carolina Pakpahan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Speaking is one of the most essential skills in learning English; however, many students still experience difficulties in developing and organizing their ideas in spoken communication. Therefore, appropriate instructional strategies are needed to improve students’ speaking performance, particularly in terms of content and organization. This study aimed to investigate the effect of using vlogging tasks on students’ English speaking performance at SMA Gajah Mada Medan. This research employed a quantitative experimental design using two groups: an experimental group and a control group. The sample consisted of 40 eleventh-grade students, with 20 students in the experimental group and 20 students in the control group. The experimental group was taught using vlogging tasks, while the control group received conventional speaking instruction. The instrument used in this study was a speaking performance test assessed based on two macro-skill aspects, namely content and organization. The result of the data analysis showed that the mean score of the experimental group increased significantly from 47.5 in the pre-test to 78.5 in the post-test, while the control group improved from 42 to 51. Furthermore, the gain score of the experimental group was 30.5, which was higher than the control group’s gain score of 9. The result of the Independent Sample T-Test showed that the significance value (Sig. 2-tailed) was 0.000 (p < 0.05), indicating that the alternative hypothesis (Ha) was accepted. Based on the findings, it can be concluded that the use of vlogging tasks has a significant effect on students’ English speaking performance, particularly in improving the aspects of content and organization.